Strategi Pembelajaran Lembaga Kursus Bahasa Arab Al Azhar Pare Kediri dengan Penerapan Metode Inovatif - Zuhdi, Bagus; Tyas, Zuhriana Widya Rahayu Ning; Hikmawati, Hanifah (LP. Ma'arif Janggan Magetan, 2024)
This research focuses on the learning strategies of Al-Azhar Pare Kediri Arabic Course Institute to improve students' ability to practice Arabic both in terms of speaking (Muhadasah), writing (Kitabah), listening (Istima') and reading (Qiraah) using innovative methods. The majority of students have learned Arabic properly so that many of them managed to continue their studies in the Middle East and develop Arabic after studying at Al-Azhar Pare Kediri. The results showed that the learning strategy at Al-Azhar Pare Kediri is very structured, both in terms of learning materials and in the readiness of teachers to provide innovative methods to create an interesting and fun learning atmosphere, besides that students can choose Arabic course programs that suit their abilities and expertise.